2016
DOI: 10.1182/blood-2015-05-644260
|View full text |Cite
|
Sign up to set email alerts
|

A CCR2 macrophage endocytic pathway mediates extravascular fibrin clearance in vivo

Abstract: Key Points• Fibrin is cleared from extravascular space via endocytosis and lysosomal degradation by a CCR2-positive subset of inflammatory macrophages.• This novel endocytic fibrin degradation pathway is mechanistically coupled to extracellular fibrin degradation pathways.Extravascular fibrin deposition accompanies many human diseases and causes chronic inflammation and organ damage, unless removed in a timely manner. Here, we used intravital microscopy to investigate how fibrin is removed from extravascular s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 88 publications
1
33
0
Order By: Relevance
“…The degradation of such non-collagenous ECM proteins may also involve endocytosis (Motley et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…The degradation of such non-collagenous ECM proteins may also involve endocytosis (Motley et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…Much evidence showing that macrophages can respond to CCL2 also comes from studies done on osteoclasts, which are tissue-resident macrophages (102)(103)(104)(105). Concluding, it seems that macrophages represent a wide spectrum of differently polarized cells wherein some subsets do express CCR2 and are able to respond to CCL2 while others do not (171)(172)(173). Regulation of cell expression of this chemokine receptor may represent a neat way of controlling site-specific macrophage responses to CCL2.…”
Section: Considerations Regarding Ccl2's Impact On Myeloid Cellsmentioning
confidence: 99%
“…When investigating BMDMs (M-CSF derived) and BMDCs (GM-CSF derived) generated from CCL2 knockout and CCR2 knockout mice, Chen et al found reduced phagocytosis (of Escherichia coli) and endocytosis (of dextran) compared to BMDMs of wild-type mice (108). Furthermore, the CCL2/CCR2 axis seems to be essential for macrophage-mediated endocytosis of collagen and fibrin (111,171). This ECM turnover is critical during tissue remodeling and repair (197).…”
Section: Increase Of Phagocytosis Efferocytosis and Endocytosis Ofmentioning
confidence: 99%
“…In healing wounds, the plasma-derived ECM is cleared through extracellular proteolysis by fibrinolytic enzymes (59) and through endocytosis by CCR2 + macrophages (60). In the healing infarct, clearance of the fibrin-based provisional matrix by the plasminogen/plasmin system is an important part of the reparative response.…”
Section: Ecm During the Proliferative Phase Of Infarct Healingmentioning
confidence: 99%